Peningkatan Motivasi dan Prestasi Belajar IPA Materi Gejala Alam melalui Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) Siswa Kelas VIIG SMP 3 Jekulo Kabupaten Kudus Semester 2 Tahun 2012/2013 - Purwaningsih, Sri; Purniawati, Ida (widiyanto, 2015)
The research objective of this class action is to determine whether the model type STAD cooperative learning can increase the motivation to learn science for students of classes VII G SMP 3 Jekulo district on the materials of symptoms nutare and can determine the increase learning achievement in science for students of classes VII G SMP 3 Jekulo districts the material of symptom nature. This study was conducted over seven months starting from the beginning of November 2012 until May 2013. The results of this study states through cooperative learning STAD (Student Team Achievement Division) can increase the motivation to learn science Symptom nature from the initial condition low learning motivation to conditions high-end motivation to learn science. From the results of the study also mentions through cooperative learning STAD (Student Team Achievement Division) can improve learning achievement Symptom nature on the material of the initial conditions of learning achievement averages 47.5 to the final conditions mean 76.32. It can be concluded both theoretically and empirically that cooperative learning STAD (Student Team Achievement division) can improve learning achievement.